ANALYZING THE IMPACT OFF TRAUMA ON MENTAL HEALTH: AN ISLAMIC PSYCHOLOGY PERSPECTIVE - Bayu Brhawijaya; Atria Afrilanti; Refola Ezi; Sugeng Sejati (Universitas Negeri Surabaya, 2025)
This research holds significant value in addressing the gaps in the literature on trauma and mental health, particularly in the context of Islam. By integrating Islamic values into mental health interventions, it is expected to offer a more comprehensive and culturally appropriate approach for Muslim trauma survivors. The method used in this study is a qualitative approach through literature review, which includes analysis of related articles, including studies on the impact of childhood traumatic experiences and the effects of past trauma on mental health. The findings of this research indicate that mental health, according to Islamic teachings, means being free from mental issues and being able to adapt to the social environment, while also emphasizing the importance of patience and devotion to Allah in facing life's challenges. This study focuses on investigating the relationship between traumatic experiences and mental health, as well as evaluating the effectiveness of interventions based on Islamic values in the healing process